호주 원주민 공동체 아카이브와 '평행출처주의'의 현재적 의미 - 이경래; Lee, Kyong Rae (기록학연구, 2014)
The purpose of this study is to trace the formation process of "parallel provenance" concept in the context of Australia's aboriginal community archives development and draw its implications for contemporary rebuilding of domestic "past affairs-related committee archives". Focused on historical development of aboriginal community archives in Australia, this writing divides its development into three periods: colonial archives, post-colonial archives, and contemporary archives and investigates each period's distinct features in managing and building of aboriginal community archives. First of all, for colonial archives, it pays attention to Australia's archival tradition, which focused on current record-keeping and then development of multiple provenance resulted from this tradition. Second, for post-colonial archives, it examines the appearance of aboriginal people as the subject of documentation category and name indexing on them. Finally, for contemporary archives, it analyzes current activities of Australia's academic world of archival science for overcoming "the otherness" of aboriginal people through conceptualization of "parallel provenance". Conclusively, through current meaning of parallel provenance, this study draws implications for democratic contemporary rebuilding of domestic past affairs-related committee archives, in which historical victims become the subject of archives. 본 논문은 호주의 원주민 공동체 아카이브 사례를 중심으로 발전한 '평행 출처주의'의 형성 과정을 추적하고, 이것이 국내 과거사 아카이브의 기록화 과정에 어떤 함의를 가질 수 있는지를 고찰했다. 이 글은 호주 원주민 공동체 아카이브의 역사적 발전을 중심에 놓고, 그 시기를 크게 식민주의 아카이브, 후기식민주의 아카이브, 그리고 동시대 아카이브로 구분했다. 각 국면 분석을 통해 본 연구는 호주원주민 공동체 아카이브의 관리 및 구축 방법에 있어서 고유한 특성들과 원주민 아카이브의 진화 과정을 살폈다. 즉 식민주의 아카이브에서는 백인 관료들이 생산한 현용 행정기록 중심의 아카이브 전통과 그로 인한 다중 출처주의의 발전에 주목했다. 후기 식민주의 아카이브에서는 기록화 범주로서 호주원주민의 등장과 이들에 대한 인명 색인 작업에 대해 비판적으로 검토하였다. 마지막으로 동시대 아카이브에서는 호주 원주민의 타자화를 극복하기 위한 호주 기록학계의 최근의 움직임을 '평행 출처주의' 개념을 통해 살펴보았다. 결론에서는 이 개념의 현재적 의의를 통해 그동안 역사에서 재현되지 못한 피해당사자들이 주체가 되는 국내 과거사아카이브의 민주적인 동시대적 재구성을 위한 함의를 도출하고자 했다.